Dietary fiber and fermentability characteristics of different pili (canarium ovatum engl.) varieties in the Philippines - Millena, Cristopher G.; Altavano, Bernardo A.; Sagum, Rosario S. (Vol. 150, No. 4 (August 2021) pages 845-855.)
"Pili nut (Canarium ovatum Engl.) is an indigenous fruit-bearing tropical tree nut in the Philippines. This study determined the dietary fiber and in vitro fiber fermentability characteristics of the pulp and kernel of seven approved Pili nut varieties that are cultivated in single soil conditions. The Pili nut pulp is an excellent source of dietary fiber (4.18-14.5 g/ 100 g soluble fiber; 34.0-43.2 g /100 g insoluble fiber), while kernel contributes a considerable amount"-Title page.